Impact of the COVID-19 pandemic on the digitization of routine pediatric practice in Spain: A nationwide survey study - Martín-Masot, Rafael; Diaz-Martin, Juan J.; Santamaría-Orleans, Alicia; Navas-López, Víctor Manuel (Frontiers in Pediatrics, 2023)
Introduction The COVID-19 pandemic forced a change in the working dynamics of all healthcare professionals, leading to the sudden introduction of telemedicine. Although until that moment telemedicine applications had been described in the paediatric age, their use was anecdotal. Objective To analyse the experience of Spanish paediatricians after the forced digitization of consultations due to the pandemic. Methods A cross-sectional survey-type study was designed to obtain information from Spanish paediatricians about the changes that took place in the usual clinical practice. Results 306 health professionals participated in the study Most of them agreed on the use of the internet and social networks during the pandemic, referring to mail or WhatsApp® as usual channels of communication with their patients' families. There was a great agreement among paediatricians that the evaluation of newborns after hospital discharge and establishing methodologies that allow childhood vaccination and the identification of subsidiary patients for face-to-face evaluation were necessary although the limitations of the lockdown. The idea that telephone and digital consultations have optimized the consultation time and that they will probably continue after the end of the pandemic was generally accepted. No changes in adherence to breastfeeding or the start of complementary feeding were referred to, but an increase in the duration of breastfeeding and the appearance of frequent hoaxes in social networks concerning infant feeding were found. Conclusions It is necessary to analyse the impact of telemedicine in paediatric consultations during the pandemic to evaluate its effectiveness and quality to maintain it in routine paediatric practice.